1990
DOI: 10.2136/sssaj1990.03615995005400030016x
|View full text |Cite
|
Sign up to set email alerts
|

Cation Exchange Isotherms Obtained with Batch and Miscible‐Displacement Techniques

Abstract: In order to predict the transport of reacting solutes through soils, it is necessary to quantify their partitioning between the solution and surface phases. Conventional batch techniques for measuring adsorption isotherms have limitations for many surface reactions, which may be overcome by using miscible‐displacement methods. In this study, an improved miscible‐displacement technique for measuring adsorption isotherms was developed and its results compared with those from a standard batch method for cation ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…The sorption behavior in batch and column studies has been found to be in agreement in some studies (Bond and Phillips, 1990;Gaber et al;1992;Hanna et al, 2009). Miller et al (1989 showed however higher distribution coefficients for column methods.…”
Section: Relevance Of the Difference Between Batch And Column Experimsupporting
confidence: 81%
“…The sorption behavior in batch and column studies has been found to be in agreement in some studies (Bond and Phillips, 1990;Gaber et al;1992;Hanna et al, 2009). Miller et al (1989 showed however higher distribution coefficients for column methods.…”
Section: Relevance Of the Difference Between Batch And Column Experimsupporting
confidence: 81%
“…A miscible displacement technique 14 is used to measure equilibrium adsorption instead of a conventional batch technique due to some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…The Gaines-Thomas selectivity coefficient is constant if corrected for activity coefficients of ions in solution (e.g., see Ref. [6]). In general, Eq.…”
Section: Resultsmentioning
confidence: 99%